Faktor risiko musculoskeletal disorders pada operator jahit wanita - Citra Handiayudya Laras Ati; Wartini Wartini; Nur Ani; Syefira Ayudia Johar (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: The garment industry is a crucial manufacturing sector, with the majority of female workers performing static and repetitive sewing activities. Unergonomic work postures have the potential to cause musculoskeletal disorders (MSDs). Initial observations revealed that 30 female sewing operators sat with hunched backs, raised shoulders, and feet continuously pressing on the machine pedals. This condition requires immediate intervention, delay in action can lead to permanent disability and directly disrupt factory operational stability and productivity. Purpose: To analyze risk factors for musculoskeletal disorders in female sewing operators. Method: This is an observational analytical study using a cross-sectional approach. The sample was selected using a simple random sampling technique. The study population consisted of 259 female sewing operators at Sinta Pertiwi Klaten Limited Liability Company. The Slovin formula was used for sampling and a 5% margin of error, resulting in 157 samples. This study was conducted in the fourth week of May 2026. The Rapid Entire Body Assessment (REBA) method was used to assess work posture, and MSD complaints were measured using the Nordic Body Map (NBM) questionnaire. The data were then analyzed using the non-parametric Spearman's rank sum test. Results: The majority of respondents (97.5%) had risky work postures (153 respondents), and 66.9% (105 respondents) experienced painful MSDs. Bivariate analysis showed no significant association between work posture and musculoskeletal disorders (MSDs), with a p-value of 0.156 (P > 0.05). Conclusion: Work posture is not a significant factor in the incidence of musculoskeletal disorders (MSDs). Individual factors, such as young age, normal body mass index (BMI), less than 5 years of service, not smoking, and exercise habits or overall lifestyle, were more dominant influences on MSD complaints. Keywords: Female Tailors; Musculoskeletal Disorders; Work Posture.